Peculiarities of Investigating Criminal Offenses Related to Illegal Turnover of Narcotic Drugs, Psychotropic Substances, Their Analogues or Precursors: Criminal Law Aspect - Maksym Korniienko; Anatolii Desyatnik; Galina Didkivska; Yevhen Leheza; Oleksiy TitarenkÐ¾ (Khazanah Hukum, 2023)
The article highlights the legal regulation of peculiarities concerning investigation of criminal offenses related to the illegal turnover of narcotic drugs, psychotropic substances, their analogues or precursors.. Main content. It has been established that effectiveness of pre-trial investigation in criminal proceedings on the facts of illegal sale of substances excluded from free circulation using the Internet and other telecommunication technologies is complicated by the need to identify the user under a nickname. Methodology:Â  The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method as well as methods of analysis and synthesis. Conclusions. It has been established that Â in todayâ€™s conditions, against the background of the global IT development of society and the active introduction of the latest technologies in all spheres of human life, the forms of sale of narcotic drugs, psychotropic substances, their analogues or precursors are also changing. While using the assets of modern technologies criminals constantly improve their criminal activities, change directions of interaction with the aim of committing offenses. In Ukraine, as well as in the world in general, drug crimes are actively carried out through smartphones via the â€œInternetâ€ network using messengers and special applications for the distribution of psychoactive substances, narcotic drugs and their analogues.